Rapid room temperature degradation of carbon nanotubes by sodium hypochlorite and UV-light irradiation. (May 2023) - Yang, Mei; Iizumi, Yoko; Chen, Liang; Okazaki, Toshiya; Futaba, Don; Zhang, Minfang
Abstract: Due to their unique graphitic tubular structures, carbon nanotubes (CNTs) are chemically and mechanically stable, and thus not easily degradable, which is a major safety concern for their wide and environmentally friendly use. In this study, we report the rapid degradation of single-wall CNTs (SWNTs) into carbon dioxide at room temperature using sodium hypochlorite (NaClO) and UV-light irradiation (UV/NaClO). The results showed that SWNTs could be degraded within 1–2 h, compared with >1 week without light irradiation. No obvious light dependence was observed for SWNT degradation using monochromatic light sources at 245 nm, 365 nm, and 305 nm. Raman and Fourier-transform infrared spectroscopies and scanning electron microscopy with energy dispersive spectroscopy revealed that degradation of SWNTs involved a multi-step oxidation reaction. Irradiation of NaClO induced the formation of oxygen radicals, which reacted with SWNTs to generate epoxy and ether groups. These groups then reacted with the oxygen radicals to form carboxylic groups, which introduced defects into SWNTs. Carboxylic and/or ether groups were directly transformed to CO2, or into intermediate products such as ethylene glycols, as oxidation progressed. The findings improve our understanding of the stability of CNTs and demonstrate a potential route for the rapid treatment of CNT wastewater for safe handling, disposal, and risk management. Graphical abstract: Image 1